Comparison of the Effect of Three Types of Iron Drops on Surface Roughness of Deciduous Teeth in a Simulated Cariogenic Environment - Eskandarian, Tahereh; Motamedifar, Mohammad; Hekmatfar, Somayeh; Tamaddon, Ali Mohammad (Journal of Dental School, 2020)
Objective: Iron deficiency anemia is among the most common types of childhood anemia. According to the World Health Organization, approximately 5 billion people were suffering from iron deficiency anemia worldwide in 2001. Aside from causing anemia, iron deficiency can negatively affect the physical and mental development of children and adolescents. Several studies have discussed the consequences of inadequate iron intake among which we may name changes in deciduous teeth. Considering the importance of iron supplementation, the present in-vitro study aimed at assessing the surface roughness of deciduous teeth following exposure to three different iron drops. Methods: This in-vitro experimental study was conducted on 90 sound anterior deciduous teeth that were divided into 6 groups. After surface preparation, the teeth were placed in cariogenic environment. Different ferrous sulfate compounds were added to 4 media and the remaining two groups were considered as positive and negative controls. Fourteen days later, the specimens were removed from the media, sectioned labiolingually, polished and enamel and dentin microhardness were evaluated. The mean microhardness value for the 15 specimens in each group was recorded. ANOVA was applied for comparison of data and LSD test was used for multiple comparisons. Results: No statistically significant differences were found in enamel microhardness of the 6 understudy groups. The mean microhardness of dentin was significantly different in the three understudy depths. Dentin microhardness immediately below the DEJ, at 250 Mm distance from the DEJ and at 450 Mm distance from the DEJ was (kgf/m2) 68.72 (10.00), 67.75 (8.75) and 68.75 (11.86) in group 1, 69.22 (12.46), 73.06 (9.36) and 69.29 (8.01) in group 2, 68.533 (12.27), 64.63 (10.64) and 69.64 (10.15) in group 3, 83.033 (11.22), 71.68 (16.01) and 70.88 (17.60) in group 4, 60.080 (9.83), 63.52 (14.46) and 65.49 (11.20) in group 5 and 91.91 (43.76), 88.62 (20.47) and 85.04 (26.56) in group 6 (p=0.001 for all three), respectively. Pair-wise comparison of groups revealed that the mentioned difference is due to the statistically significant differences between group 6 and other groups and the remaining groups were not significantly different. Conclusion: This study showed that iron supplementation had no effect on demineralization of tooth structure.